Short-term clinical and radiographic outcomes of a 3D-printed trabecular titanium acetabular cup in primary total hip arthroplasty for Crowe type I–III developmental dysplasia of the hip with limited acetabular bone defects: a retrospective comparative study - Chengxiao Li; Lilei Song; Junheng Zhang; Bo Liu; Zhaolong Wang; Yongqiang Fan; Binquan Zhang; Yiding Liu; Kun Xiang; Yifan Niu; Guangyang Lu; Huijie Li (Frontiers in Medicine, 2026)
Objective To compare the short-term clinical and radiographic outcomes of a 3D-printed trabecular titanium acetabular cup system (AK Medical, Beijing, China) with a conventional porous titanium-coated acetabular cup system (Pinnacle Gription Sector Acetabular System, DePuy Synthes/Johnson & Johnson, USA) in primary total hip arthroplasty (THA) for Crowe type I–III developmental dysplasia of the hip (DDH) with limited acetabular bone defects not requiring metal augments or structural bone grafting. Methods This retrospective study included 104 patients (105 hips) who underwent primary THA for DDH between January 2022 and July 2023, including 51 hips in the 3D-printed trabecular titanium cup group and 54 hips in the conventional porous titanium-coated cup group, with a mean follow-up of approximately 24 months. The primary outcome was the proportion of cups meeting at least 3 of the 5 Moore radiographic criteria at final follow-up, with early revision classified as failure of the index cup. VAS and HHS were analyzed using patient-clustered generalized estimating equations (GEE). The primary radiographic endpoint was compared using Fisher's exact test, with stabilized inverse probability of treatment weighting (IPTW) used as an adjusted sensitivity analysis. Results Operative time, intraoperative blood loss, length of stay, and postoperative acetabular cup position parameters were similar between groups. VAS scores were lower in the 3D-printed cup group at 1 week, 1 month, and 3 months postoperatively. A significant group-by-time interaction was observed for HHS; HHS was higher in the 3D-printed group at 1 and 6 months, the between-group difference at 3 months did not reach statistical significance, and outcomes were similar between groups from 12 months onward. In the primary analysis, which conservatively classified early revision as failure, the proportions meeting the prespecified final-follow-up radiographic criterion were 46/51 (90.2%) and 40/54 (74.1%), respectively ( P = 0.042; crude OR = 3.22, 95% CI: 1.07–9.73). After stabilized IPTW, the weighted proportions were 92.9% and 75.7%, with a weighted OR of 4.21 (95% CI: 1.35–13.17, P = 0.013). In the serial-radiograph subset of 82 hips, the proportions meeting the ≥3/5 Moore criterion at 3 and 6 months were similar between groups and increased over time; P for the group-by-time interaction was 0.097. Complication events were infrequent, and safety findings were interpreted descriptively. Conclusion In primary THA for Crowe type I–III DDH with limited acetabular bone defects not requiring augments or structural bone grafting, the 3D-printed trabecular titanium acetabular cup system was associated with a higher proportion of hips meeting the final-follow-up radiographic integration endpoint and with better early VAS and HHS outcomes. No clear early between-group difference in the radiographic endpoint was observed at 3 or 6 months. This study compared two specific implant systems; longer follow-up is required to evaluate long-term fixation and implant survivorship.